Entropy controlled phase transitions - Sampedro Ruiz, Pablo (Nanyang Technological University, 2020)
A fundamental part of the design of new materials lies in the study and control of the phase transitions of solids. This control implies tweaking the free energies of the different phases of the material, in order to stabilize those we are interested in or destabilize those we are not. Although classically it has been understood that the formation of new solids is driven by enthalpic factors, entropy supposes a new and promising tool in the field. This kind of approach offers us a simpler design of assembly particles and a more reliable process. In this thesis we study the effect entropy can have in the self-assembly of colloids, by applying this approach to two experimental colloidal systems (mDNACCs and 2D hard spheres), as well as presenting a new computational method designed for the study of the assembly of spherical colloids.